Folded chordal graphs - McKee, Terry A. (Utilitas Mathematica, 1999)
Applications of chordal graphs to seriation and filiation problems are based on intersection graphs of connected subgraphs of (respectively) paths and trees. "Folded chordal" graphs extend these applications by requiring only that the subgraphs be "plausibly connectable," meaning that gaps between components can in a sense be bridged by other relevant connected subgraphs.